Mesir dan Pembaharuan Pemikiran Politik Islam : Rekam Jejak Sayid Jamaluddin Al-Afghani - Fakhruddin, Ahmad Shiddiq (Tumanurung: Jurnal Sejarah dan Budaya, 2025)
Jamaluddin al-Afghani was a political reformer of Islamic thought. He was born in Afghanistan and spent his life in various Muslim countries and Europe. This research aims to discuss Egypt in the 19th century (social and political conditions), al-Afghani's life journey and thoughts, and discuss the notion of modernity in Islam. The type of research used in this research is library research. The results of the research are a description of the condition of Egypt at the beginning of its rise, al-Afghani's journey and his various movements in the political field in Egypt, and the concept of modernity in Islam and al-Afghani's thoughts on modernity. Jamaluddin al-Afghani left many thoughts that became a reference for thinkers and reformers in the future.